POTENSI LUMPUR LAPINDO SEBAGAI BAHAN BAKU TAMBAHAN PEMBUATAN BATU BATA - Rofikatul Karimah (Jurnal Gamma, 2010)
The case of the devastating flood of hot mud from gas drilling PT. LAPINDO Brantas inPorong Siring village of Sidoarjo regency of East Java on 29 May 2006 caused tremendous lossimpact. Puddle and a large volume of mudflow an issue as well must be immediately sought a wayto use it. Business of mud matching is the manufacture of building materials, especially materials ofred brick. It is based on UMM Lumpur research Team (2006) that the Lapindo mud can be used asan ingredient brick-making raw because they contain clay. This study aims to gain prototype madeof mud bricks in accordance with the level / class of bricks.This study is an experiment, the experimental design "One Group Pretest-posttest Design ". Inthis study independent variables consisted of percentage mud in clay 0%, 10%, 15%, 20%, 25%,30%, 35%, 40% and the dependent variable compressive strength, water absorption and solid brickattached brick.Research results indicate brick class I achieved on the percentage of mud in clay 15% to 25%.While the percentage of sludge 0%, 10%, 30%, 35% will produce bricks class II and the percentageabove 35% would produce a level lower bricks of stone normal brick. Water absorption value ofless than 20% brick for brick made of mud above 20% thus require immersion in water beforeinstallation. While the percentage of 0%, 10%, 15%, water absorption value of less than 20% brick,the brick does not require installation submersion.